Designing a Framework to Control ?the Spread of Covid-19 by Utilizing ?Cellular System - Awder Mohammed Ahmed (Kurdistan Journal of Applied Research)
Nowadays coronavirus (Covid-19) has become a concerning issue in the world, according to WHO latest report more than 8,000000 of people in our planet have been infected and more than 400000 of people have died until the writing of this paper. Everybody on this planet is exposed to get this pandemic. Scientists, organizations, governments, and universities around the world endeavor to ?find proper solutions to control the spread ?of covid-19. Thus, the aim of this paper is to propose an applicable framework to control the spread of Covid-19 by utilizing Cellular System. This is done by Haversine formula to calculate the distance between mobile phones based on cell towers. And it can also be fulfilled via designing a framework which is composed of four phases. Phase 1, deals with distance calculation and data collection about the infected and suspected persons. Then in phase 2, the Authorized Clinical Center (ACC) delivers the ID of the infected person to the Telecom Company (TC) to gather information about the unknown suspected persons. In turn, phase 3 diagnoses the infected persons and informs them to visit the ACC. In the last phase, the suspected persons are tested and the infected ones are recognize.